Numerical Simulation for the Bell Directivity Patterns Determination - GOŁAŚ, Andrzej; FILIPEK, Roman (Archives of Acoustics, 2009)
The analysis of various sound sources is performed on the basis of their directivity patterns. The literature does not contain any information about directivity patterns of bells that are instruments broadly applied to sacral purposes or to create a certain sound space from the aesthetic point of view. The paper presents the methodology of determining the bell directivity patterns by an example of the Russian bell. This example was applied because exact values of geometrical parameters and measuring data of the bell were available. The model was created by means of FEA (finite element analysis). It included a coupling between the bell and its surrounding acoustic medium. During the modal analysis, the first three natural frequencies of the bell were calculated, and then, using the harmonic analysis, the directivity patterns were determined for the frequencies. Afterwards, the transient response of the system in selected measuring points was determined. The obtained results are important for bell-founders and architects because thanks to the knowledge of directivity patterns, the constructions supporting the bells can be designed in a better way and the sound propagation can be determined more precisely. The presented method of auralisation of the bell sound makes the cooperation between the designer and the receiver fairly convenient.